2021
DOI: 10.1021/acs.chemrev.1c00196
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-type Protein Aggregation and Prion-like Properties of Amyloids

Abstract: This review will focus on the process of amyloid-type protein aggregation. Amyloid fibrils are an important hallmark of protein misfolding diseases and therefore have been investigated for decades. Only recently, however, atomic or near-atomic resolution structures have been elucidated from various in vitro and ex vivo obtained fibrils. In parallel, the process of fibril formation has been studied in vitro under highly artificial but comparatively reproducible conditions. The review starts with a summary of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 278 publications
4
127
0
Order By: Relevance
“…Recently, with the advance in state-of-the-art structural biology techniques and equipment, several new fibril structure details have been reported at atomic and near-atomic level (for review see ref. [ 71 ]). It is quite bewildering to note the differences in handedness, fibrillar length, helical axis position, and pitch length.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the advance in state-of-the-art structural biology techniques and equipment, several new fibril structure details have been reported at atomic and near-atomic level (for review see ref. [ 71 ]). It is quite bewildering to note the differences in handedness, fibrillar length, helical axis position, and pitch length.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, peptide oligomers organize in β-sheet structures, which lead to the sequential formation of protofilaments, then fibrils, and finally amyloid plaques [ 42 , 43 , 44 ]. The investigation of the mechanisms leading to amyloid fibrillization has helped in the identification of the short KLVFF motif of the Aβ40 and Aβ42 fragments as the factors responsible for the first steps of peptide aggregation [ 45 , 46 ]. With a reductionist approach, Gazit and co-workers used the FF dipeptide to engineer a variety of nanostructures (tapes, nanotubes, fibrils, etc.)…”
Section: The Bottom-up Approach To Hierarchical Self-assemblymentioning
confidence: 99%
“…These fibrous deposits have been linked to systemic and neuro-debilitating diseases, such as atherosclerosis, Alzheimer's, Parkinson's, and others. 171,172 Curiously, on the other hand, experimental studies have suggested that EMFs may be used as a therapeutic tool for the breakdown of fibrils implicated in Alzheimer's disease. 15,57 Therefore, an improved understanding of the effects of radiofrequency radiation on biomolecules and their implications in disease processes at the molecular level has been the goal of several research groups.…”
Section: Recent Case Studiesmentioning
confidence: 99%